1994
DOI: 10.1115/1.2904281
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Analysis of Electromagnetic Forming for Tube Expansion

Abstract: The electromagnetic field and dynamic deformation analyses for tube expansion by electromagnetic forming were performed by the finite element method. A realistic pressure distribution was calculated by taking into account both coil and workpiece. The calculated values of displacement along the tube axis and with time were in very good agreement with the measured ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Our theory can be applied for nonaxially symmetric geometries as well. However, for these more general geometries the pertinent differential equations, both the electromagnetic and elastic ones, have to be solved by numerical methods, e.g., a finite-element method developed by Lee et al [19], [20] and Besbes et al [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our theory can be applied for nonaxially symmetric geometries as well. However, for these more general geometries the pertinent differential equations, both the electromagnetic and elastic ones, have to be solved by numerical methods, e.g., a finite-element method developed by Lee et al [19], [20] and Besbes et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that, when no matter is present in , both terms will vanish. As a consequence, in (19) and (20) can be conjectured to be the driving volume source densities of body force in the elastodynamic field equations that govern the behavior of dynamic stress and particle velocity in mechanically deformable matter. In conclusion, we have found that in an inhomogeneous medium, the total volume force consists of two forces; see (19)- (20).…”
Section: Electromechanical Volume and Surface Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is obtained as (16) A special case in the calculation of the Green's function is represented by . For this case, we have for for for (17) The general solution of (8) is given by (18) where the coefficients and are obtained from the boundary conditions (19) with from (16). Thus, the coefficients and may be calculated as (20) With the particular solution in (10) and with the general solution in (18), the solution for in (9) is obtained.…”
Section: Temperature Distributionmentioning
confidence: 99%
“…Recently, the numerical simulation method has become more and more widely used in the analysis of magnetic pressure in electromagnetic forming. And it is reported that the precision of the results is greatly enhanced [4,5].…”
Section: Introductionmentioning
confidence: 96%